A bulk and fraction-specific geochemical study of the origin of diverse high-grade hematitic iron ores from the Transvaal Supergroup, Northern Cape Province, South Africa - Moloto, William (Rhodes University, Faculty of Science, Department of Geology, 2017)
The Paleoproterozoic Transvaal Supergroup in the Northern Cape Province of South Africa is host to high-grade, Banded Iron Formation-hosted hematite iron-ore deposits and is the country's most important source of iron to date. Previous studies suggest the origin of these iron ores to be ancient supergene, and that the ore forming process would have therefore pre-dated deposition of the basal Mapedi shales of the Olifansthoek Supergroup that unconformably overlies the Transvaal strata. The nature of the protolith to the ores has been suggested to be largely BIF of the Asbestos Hills Subgroup, and mainly the Kuruman BIF. The work presented in this thesis seeks to provide insights into the diversity of processes that are likely to have been involved during the genesis of these high-grade iron ores, in the context of constraining the pre-ore lithologies and the relative role of supergene-style, largely residual enrichment processes versus any possible metasomatic hydrothermal effects. This study had as primary focus the application of combined bulk and fraction-specific geochemical applications on representative iron-ore samples from four different localities in the Northern Cape Province, namely King/Khumani, Beeshoek, Heuninkranz and Hotazel. The collected samples show a variety of textures and also capture different pre-unconformity stratigraphic sections of BIF. The key objective was to assess whether the fraction-specific analytical results could provide any firm constraints for the origin of the ferrous and non-ferrous matrix fractions of the ores, namely whether they represent any combinations of protolith residue, allochtonously-introduced detritus or hydrothermally-derived material, and whether the results are comparable and consistent across all samples studied. In particular, constraints were sought as to whether the ore protolith was exclusively BIF or may potentially have contained at least a fraction of other lithologic types, such as shale; and whether there is sufficient evidence to support solely a supergene model for the ores or the data suggest other more epigenetic models of ore formation involving the action of hydrothermal fluids Bulk-rock geochemical analyses reveal the overwhelming dominance of Fe-oxide (as hematite) in all samples, at concentrations as high as 99 wt.% Fe2O3. Major and trace-element abundances of all samples were re-calculated assuming only iron addition from the postulated protolith (average BIF and shale), and the results revealed atypical enrichments in the iron ores by comparison to average BIF, and more shale-like relative abundances when normalised against the Post-Archaean Average Shale (PAAS). Specifically, BIF-normalised diagrams show relative enrichments by as much as 53-95% for Al2O3; 11-86% for TiO2; and 4-60% for P2O5. By contrast, PAAS-normalised values display enrichments of 1-3% for Al2O3, 0.2-3% for TiO2, and 3-13% for P2O5. Similar observations can be made for the greatest majority of trace elements when normalised against average BIF as compared to normalisation against PAAS. A suite of trace element that include alkali earths (e.g. Ba, Sr) and transition metals (e.g. Ni, Zn) show enrichments that are unrelated to the apparently detrital siliciclastic fraction of the ores, and are therefore linked to a possible hydrothermal input. Fraction-specific extractions were performed via the adaptation of existing dissolution protocols using oxalic acid (iron-oxide fraction) followed by HF digestion (silicate-fraction). The analyses of the produced aliquots using ICP-MS techniques, focused mainly on the REE abundances of the separated ferrous and non-ferrous matrix fractions and their comparisons to bulk-rock REE signatures. The results lend further support to the suggestion that the ore samples contain a predominant shale-like signal which does not directly compare to published REE signatures for supergene or hydrothermal BIF-hosted iron-ore deposits alike. The data therefore collectively point to a post-unconformity epigenetic hydrothermal event/s of iron ore-formation that would have exploited not only BIF but also shale as suitable pre-ore protolith.
Keywords: Iron ore -- South Africa -- Transvaal Supergroup; Hematite -- South Africa -- Transvaal Supergroup; Transvaal Supergroup (South Africa)